Dietary supplementation with cysteine prevents adverse metabolic outcomes of repeated cures with paracetamol in old rats. Issue 11 (27th November 2017) - Mast, Carole; Pourpe, Charlène; Voyard, Guillaume; Rémond, Didier; Migné, Carole; Centeno, Delphine; Dardevet, Dominique; Savary-Auzeloux, Isabelle; Papet, Isabelle
Abstract: Cysteine (Cys), a conditionally indispensable amino acid, is required for the detoxification of paracetamol (acetaminophen, N -acetyl- para -aminophenol, 4-hydroxy-acetanilide, APAP), a drug of widespread use in older persons. We recently reported that repeated APAP cures could worsen sarcopenia in old rats, likely to be due to the impairment of Cys/GSH homoeostasis. The aim of the study was to evaluate whether a dietary Cys supplementation during APAP cures could improve Cys/GSH homoeostasis and thus preserve skeletal muscle. Male 21·5-month-old Wistar rats received three 2-week-long cures of APAP (1 % of diet) alone or with extra Cys (0·5 % of diet), intercalated with washout periods of 2 weeks (APAP and APAP–Cys groups, respectively). They were compared with untreated control rats (CT group). CT and APAP–Cys groups were pair-fed to the APAP group. Dietary Cys supplementation was efficient to prevent increase in liver mass ( P <0·0001), decrease in liver GSH ( P <0·0001), increase in blood GSH concentration ( P <0·0001), and to some extent, decrease in plasma free Cys concentration ( P <0·05), all induced by repeated APAP cures. The addition of Cys to APAP cures decreased plasma alanine transaminase ( P <0·05), the fractional synthesis rate of liver proteins ( P <0·01), and increased masses of extensor digitorum longus ( P <0·01), and soleus ( P <0·05), compared with the APAP group. Cys supplementation prevented alteration in Cys/GSH homoeostasis and increased some muscle masses in old rats under repeated cures with a non-toxic dose of APAP.